DAYATERIMA BUBUR BAYI INSTAN DENGAN PENAMBAHAN UMBI BIT (Beta vulgaris L) SERTA KANDUNGAN ZAT GIZI - Yosephin Grace; Albiner Siagian; Etti Sudaryati (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
Beet (Beta vulgaris L) is one of the vegetables plants in Indonesia with high nutrients. Beet bulbs potentially contributes energy for humans especially infants (7-12 months). Instant baby’s porridge is one of the food products that can be made from beet bulbs. The purpose of this experiment was to determine acceptability based on organoleptic characters and to know nutrients content of instant baby’s porridge. This experiment used completely randomized design (RAL) with two treatments ; 15% and 30 % addition of beet bulbs to instant baby’s porridge. Test analysis of carbohydrate, protein, fat, crude fiber, ash and water were conducted at the Oil Palm Research (PPKS) Medan. Acceptability test is tested to 30 panelists. The results of organoleptic test were analyzed by Friedman test with 95 % confidence level. The result of nutrients content test of instant baby’s porridge with 15% addition of beet bulbsshowed levels of carbohydrate 61,97%; 11,80% protein, fat 3,62%; 3,46 % crude fiber; 3,20% ash and 4,56% water. The result of nutrients content test of instant baby’s porridge with 30% addition of beet bulbs showed level of carbohiydrate 61,17%; 12,48% protein; 3,11% fat; 4,95% crude fiber; 4,64% ash and 4,74% water.The results of organoleptic tests showed the panelists prefer instant baby’s porridge with 15 % additon of beet bulbs than 30 % additon of beet bulbs. Based on analysis by Friedman test with 95% confidence level obtained the difference in quality in terms both instant baby’s poridge in terms of colour, flavor, taste and textur. Finally through this experiment, mothers should use instant baby’s porridge with 15% addition of beet bulbs becomes alternative food for babies. Keyword : Instant baby’s porridge, beet bulbs, local food